Multisite analysis of high‐grade serous epithelial ovarian cancers identifies genomic regions of focal and recurrent copy number alteration in 3q26.2 and 8q24.3. Issue 10 (26th April 2019) - Ballabio, Sara; Craparotta, Ilaria; Paracchini, Lara; Mannarino, Laura; Corso, Silvia; Pezzotta, Maria Grazia; Vescio, Martina; Fruscio, Robert; Romualdi, Chiara; Dainese, Emanuele; Ceppi, Lorenzo; Calura, Enrica; et al.
Abstract : High‐grade serous epithelial ovarian cancer (HGS‐EOC) is a systemic disease, with marked intra and interpatient tumor heterogeneity. The issue of spatial and temporal heterogeneity has long been overlooked, hampering the possibility to identify those genomic alterations that persist, before and after therapy, in the genome of all tumor cells across the different anatomical districts. This knowledge is the first step to clarify those molecular determinants that characterize the tumor biology of HGS‐EOC and their route toward malignancy. In our study, ‐omics data were generated from 79 snap frozen matched tumor biopsies, withdrawn before and after chemotherapy from 24 HGS‐EOC patients, gathered together from independent cohorts. The landscape of somatic copy number alterations depicts a more homogenous and stable genomic portrait than the single nucleotide variant profile. Genomic identification of significant targets in cancer analysis identified two focal and minimal common regions (FMCRs) of amplification in the cytoband 3q26.2 (region α, 193 kb long) and 8q24.3 (region β, 495 kb long). Analysis in two external databases confirmed regions α and β are features of HGS‐EOC. The MECOM gene is located in region α, and 15 genes are in region β. No functional data are yet available for the genes in the β region. In conclusion, we have identified for the first time two FMCRs of amplification in HGS‐EOC, opening up a potential biological role in its etiopathogenesis. Abstract : What's new? Genomic analysis of high‐grade serous epithelial ovarian cancer (HGS‐EOC) is currently based on primary tumor testing at the time of diagnosis but tumors often relapse, and metastasis within the abdominal cavity form almost instantaneously. Here the authors analyzed spatial and temporal molecular heterogeneity in HGS‐EOC by examining not only the primary tumor but also synchronous and matched relapse lesions. Despite tumor heterogeneity, two recurrent regions of focal amplification (3q26.2 and 8q24.3) were identified. Defining the functional role of the 16 genes that map to these two genomic regions will bring new insight into the pathogenesis of HGS‐EOC and possibly define new therapeutic targets for this deadly disease.